MICROBICIDAL AND IMMUNOSTIMULATING PROPERTIES OF PLANT-DERIVED SYRUP BASED ON LIME BLOSSOM, ALTHEA ROOT AND THYME EXTRACTS - Gasimov, R.N.; Aghayeva, E.M.; Suleymanova, T.H.; Gurbanova, S.F.; Huseynov, R.M.; Narimanov, V.A.; Muradova, S.A.; Bakhishova, Y.A. (World of Medicine and Biology, 2024)
The article presents the study’s findings aimed at establish microbicidal and immunostimulating properties of the plant-derived syrop based on Lime blossom extract, Althea root extract, Thyme extract. The microbicidal properties of the preparation were examined using the disk-diffusion method, the immunostimulating properties were studied separately and in combination with the live vaccine, which contains the 1/96 strain. 400 thirty-day-old broiler chickens were included in the study and divided into four groups of 100 each: application of the vaccine (Group I) and the plant preparation (Group II), as well as their combined usage (Group III) compared to the control group (Group IV). Results showed an increase of leukocytes by 34.9±0.8, T-lymphocytes by 8.5±0.15, and B-lymphocytes by 6.35±0.8 in the blood of 3rd group chicken broilers, compared to the respective indicators of the control group (24.2±0.5, 1.75±0.20, 1.31±0.15, respectively). So, the preparation has microbicidal and immunostimulating properties in poultry complexes.